On Convergence of -Series Involving Basic Hypergeometric Series - Zhao Xilai; Wang Mingjin (Journal of Inequalities and Applications, 2009)
We use inequality technique and the terminating case of the -binomial formula to give some results on convergence of -series involving basic hypergeometric series. As an application of the results, we discuss the convergence for special Thomae -integral.